2004
DOI: 10.2169/internalmedicine.43.1107
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Amyloidosis: Heterogenous Pathogenic Backgrounds

Abstract: Cardiac amyloidosis is a fatal disorder which develops on the basis of the different pathologic conditions in systemic amyloidosis: the most common underlying disease is immunoglobulin light chain-derived primary amyloidosis and the next is transthyretin-related hereditary amyloidosis; the latter disorder, typically represented by familial amyloid polyneuropathy, was long regarded as an endemic disease. However, this disorder has now been shown to involve a highly variable clinical picture due to a large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 69 publications
(51 reference statements)
1
26
0
Order By: Relevance
“…While some TTR variants predominantly cause familial amyloidotic polyneuropathy (FAP), there are also mutations that result in a cardiomyopathy in nearly 100% of the cases such as p.Val30Met, p.Thr60Ala, p.Ile84Ser and p.Val122Ile [6,9,18]. In our series, the p.Val30Met substitution was found in two patients, which is in agreement with earlier studies describing it as one of the most common mutations [7,34]. Furthermore, this variant is known to nearly always involve the heart [9].…”
Section: Hereditary Attr Amyloidosissupporting
confidence: 91%
See 1 more Smart Citation
“…While some TTR variants predominantly cause familial amyloidotic polyneuropathy (FAP), there are also mutations that result in a cardiomyopathy in nearly 100% of the cases such as p.Val30Met, p.Thr60Ala, p.Ile84Ser and p.Val122Ile [6,9,18]. In our series, the p.Val30Met substitution was found in two patients, which is in agreement with earlier studies describing it as one of the most common mutations [7,34]. Furthermore, this variant is known to nearly always involve the heart [9].…”
Section: Hereditary Attr Amyloidosissupporting
confidence: 91%
“…The heart is affected in approximately 50% of immunoglobulin light chain-derived AL amyloidosis cases [5]. As this is a very aggressive form, affected individuals have a mean survival of 1.08 years after diagnosis [6,7]. Cardiac involvement is less frequent in transthyretinderived ATTR amyloidosis, and the prognosis is often more favorable because of a slower progression rate and a lack of toxic effects on the heart [8].…”
Section: Introductionmentioning
confidence: 99%
“…Autopsy revealed heavy deposition of amyloid on the myocardium in these two patients (22). Serious cardiac involvement by amyloid is known to be one cardinal feature in FAP patients with non-Val30Met TTR type (16,23), and this severe phenotype of cardiac amyloidosis has been suggested to be responsible for the poor post-transplant prognosis in these FAP patients. Recently, it was noted that after transplantation rapid deterioration of cardiac function with further thickening of the ventricular wall occurred in some FAP patients, although polyneuropathy and autonomic dysfunction were stabilized or slightly improved.…”
Section: Discussionmentioning
confidence: 86%
“…It has previously been reported that 41 of 1,278 patients (3.2%) with DCM have underlying amyloidosis (14). Nevertheless, case reports of DCM secondary to amyloidosis are rare (9,(15)(16)(17). The predominant deposition of amyloid in vessel walls causes microvascular stenosis or occlusion and is considered to be one of the primary mechanisms for the development of DCM in amyloidosis patients (18,19).…”
Section: Discussionmentioning
confidence: 99%